The Urgence of Culturing Aqidah in Early Childhood Based on Hadith - M. Noor Fuady (STAI Miftahul Ula Nganjuk, 2021)
The problem of education is a problem that acquires the main perioritas since the beginning of human life. Even the Prophet himself has hinted that the learning process for every human being is since he was still in his mother's womb, until the man approached his grave. In addition, with knowledge humans will be able to obtain the happiness of life in this world and in the hereafter. As a religion that prioritizes the problem of education, so throughout the life of Islam until now has emerged many experts who contribute the fruits of his mind in the field of education in particular, as well as in various other disciplines. Departing from etymological understanding in essence Islamic education cannot be separated from al-Khaliq, the Creator. Instilling aqidah in children is the responsibility of parents and is done based on the level of understanding. Planting aqidah in early childhood, which is by 1.) Instilling Prenatal Aqidah through Prayer, Dhikr Activities and Worship Together, and Fostering Compassion. Then 2.) Cultivating Post-Birth Aqidah, namely by Praying and Teaching the phrase Tawhid, Including in Worship, and Praying and Teaching Prayers